En vurdering af Euroens internationale rolle og økonomiske effekt siden indførelsen - Bertel Dons Christensen (Danish Institute for International Studies (DIIS), 2007)
– This working paper addresses the question of how the Euro has performed internationally since its introduction on the financial markets in 1999 and its introduction as a means of cash-payment in 2002. It is shown that in the period 1999-2006 the international role of the Euro grew steadily compared to the former European currencies that took part in the creation of the single currency. The paper illustrates that the increasing role of the Euro enhances the economic capacities of the Eurozone; this is illustrated among other things by the fact that the Euro has improved the seignorage and liquidity premium of the Eurozone. It is further argued that the Euro has reduced transaction costs on the markets for currency, finance and goods by making currency exchange obsolete within the single market. Besides this the Euro has made markets more transparent and prices more comparable within the Eurozone, and the Growth- and Stability Pact has ensured a policy of price stability. On the other hand, some critical arguments are put forward. These arguments are related to the fact that the Eurozone does not constitute an optimal currency area. They are also related to the derived restrictions on the economic policy of the member states related to the Growth- and Stability Pact. The paper argues that the member states have faced similar restrictions since the early 1980s and would have been likely to continue doing so in the review period, which makes the argument less relevant. In conclusion it is argued that the introduction of the Euro has enhanced the economic performance of the Eurozone. Part of the aim of the working paper is to shed light on what made twelve European countries enter an empirically atypical currency union that is historically unparalleled in proportions. Thus, it is illustrated that the economic advantages related to the introduction of the Euro can very likely explain the introduction of the single currency.
Keywords: 330